1996
DOI: 10.1093/carcin/17.3.515
|View full text |Cite
|
Sign up to set email alerts
|

Does increased endogenous formation of N-nitroso compounds in the human colon explain the association between red meat and colon cancer?

Abstract: High red meat diets have been linked with risk of sporadic colorectal cancer; but their effects on mutations which occur in this cancer are unknown. G-->A transitions in K-ras occur in colorectal cancer and are characteristic of the effects of alkylating agents such as N-nitroso compounds (NOC). We studied th effect of red meat consumption on faecal NOC levels in eight male volunteers who consumed diets low or high in meat (60 or 600 g/day), as beef, lamb or pork, whilst living in a metabolic suite. Increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
164
3
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(173 citation statements)
references
References 24 publications
5
164
3
1
Order By: Relevance
“…Bingham and colleagues conducted a human experiment where they exposed male volunteers to high amounts of red meat or heme iron. They found that these individuals produced higher levels of fecal N-nitroso compounds than when exposed to the same amounts of white meat or ferrous iron (48,49). (Fig.…”
Section: Colorectal and Colon Cancersmentioning
confidence: 97%
“…Bingham and colleagues conducted a human experiment where they exposed male volunteers to high amounts of red meat or heme iron. They found that these individuals produced higher levels of fecal N-nitroso compounds than when exposed to the same amounts of white meat or ferrous iron (48,49). (Fig.…”
Section: Colorectal and Colon Cancersmentioning
confidence: 97%
“…Red meat enhances the formation of putative carcinogenic N-nitroso compounds in human feces (8)(9)(10). But N-nitroso compounds brought into the rat intestine by a bacon-based diet did not initiate nor promote preneoplastic lesions in rat colon (11).…”
Section: Introductionmentioning
confidence: 98%
“…It has been suggested that N-nitroso compounds, present in processed meat or endogenously formed (Bingham et al, 1996), may induce G4A transitions at the second base of codon 12 or 13 of the K-ras gene in the human colon (Hughes et al, 2001). Hightemperature cooking of meat proteins generates heterocyclic aromatic amines (HAA), whereas the process of grilling and smoking of meat generates polycyclic aromatic hydrocarbons (PAH) as a result of fat dropping on open flames.…”
mentioning
confidence: 99%